EFFECT OF DIABETES SELF MANAGEMENT EDUCATION (DSME) ON KNOWLEDGE ON CONTROL OF BLOOD SUGAR ON DIABETES MELLITUS PATIENTS - lutfi wahyuni; binarti dwi wahyuningsih (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Many people who do not realize he has a disease that is more often called diabetes or diabetes. This is caused by several factors, including the level of knowledge, level of education, behavior, eating habits, closeness and exposure to information sources. One form of education that is commonly used and proven to be effective in improving the clinical outcome and quality of life of diabetes mellitus patients is Diabetes Self Management Education (DSME). This study aims to prove the influence of diabetes self-management education (DSME) to the knowledge of blood glucose control in people with diabetes mellitus in GayamanVillage and Kweden Village Work Area Health Center GayamanMojokerto. In this research the design used is Pre-experiment with One Group Pre-Post Test Design approach. The population is all DM patients in Gayaman Village and Kweden Village with 32 respondents. Samples from 32 respondents were taken using Total Sampling technique. Data collection techniques used questionnaires and data were analyzed using cross tabs. There is influence of diabetes self management education (DSME) to knowledge about controlling blood sugar level in people with diabetes mellitus with value 3,1%. Diabetes self management education (DSME) can be an intervention in providing knowledge to patients with DM, so that patients can control blood sugar levels well.